The Supranational Idea of the Peoples of Central Europe (First Half of the 19th Century) - Bevzyuk, E.; Tabanyukhova, О. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2020)
National movement and further development of national benchmarks of the European peoples at the beginning of the revolution of 1848–1849 are one of the most socio-political contextualized pages in the past of the Slavik peoples in Europe. The research is considered to be topical since the process of formation of national ideology in the 19th century, that occured in the Slavs environment, took place in terms of distribution of the national principle and state formation in the majority of the European countries. The purpose of the research is to enlighten the course, laws and specifics of formation of the national paradigm at the beginning of the revolution of 1848–1849. The object of the study is the national movement of the Slavs, the subject of scientific analysis is the national ideology developing under the influence of both internal and external factors. To achieve the main goal of the research the author has considered it to be necessary to solve a number of the following tasks: to scientifically, logically, argumentatively and coherently lay out specifics of the process of Slavic national ideology formation and reveal its main features. It should be emphasized that by the beginning of the revolution the national patriotic mood was not limited merely by the demand of the cultural reforms, it gradually transformed into the context of new political and socio-economic ideas. At the same time, in the meaning of national paradigm of the Slavic National Movement the idea of its moderation or passive opposition actualized drastically. In general, national paradigm was a certain mixture of political ideas, in which political freedom — democracy, social and personal guarantees — took a somewhat secondary place, the struggle for the national justice with its moral and cultural principles, became dominant. On the eve of the 1848 revolution western Slavs were involved in the process of modernizing their national ideology. Al though this process was an all-European phenomen on and large ethnic units were under going selfdetermination, the spiritual renaissance of the western Slavs had specific regional and ethnic characteristics, thus attracting the political attention of the governments of great empires — the Austrian and the Russian. For Russia, the biggest Slavonic country, the idea of the general Slavonic ethnic unity as well as the Pan-Slavistic ideology were not only of scientific character, but also served as a factor of geopolitical interest.